2023
DOI: 10.1111/acer.15056
|View full text |Cite
|
Sign up to set email alerts
|

Associations of state and trait empathy with daily alcohol use

Abstract: Background: A growing literature documents associations between lower trait empathy and heavier alcohol use and more alcohol problems in adolescent and young adult samples. Prior work linking empathy and alcohol use/problems in these populations has thus far focused on trait rather than state empathy, and researchers often do not differentiate between cognitive and affective empathy. Further, no prior studies have examined associations between daily fluctuations in state empathy and alcohol use. The goal of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Both routes concretize into prosocial behavior, specifically, helping that is seemingly lower in people that drink more. Thereby the resulting lower behavioral empathy might be associated with more drinking early on, suggesting that cognitive and affective pathways might become altered by alcohol in time 31 . Past studies have found both affective 22 and cognitive empathy to be low in people with AUD 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both routes concretize into prosocial behavior, specifically, helping that is seemingly lower in people that drink more. Thereby the resulting lower behavioral empathy might be associated with more drinking early on, suggesting that cognitive and affective pathways might become altered by alcohol in time 31 . Past studies have found both affective 22 and cognitive empathy to be low in people with AUD 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In line with findings in AUD populations, one meta-analysis that examined non-clinical samples found an association between lower ToM and more alcohol related problems 30 . Additionally, experimental studies in non-AUD individuals have found that drinking alcohol can have acute negative effects on social cognition processes such as facial emotion recognition, empathy and ToM (for a review, see 31 ). Consequently, low cognitive empathy (for example, due to a deficit in facial emotion recognition) can contribute to interpersonal distress, and in turn this can contribute to drinking to cope with negative affect associated with the distress 4 .…”
Section: Introductionmentioning
confidence: 99%